Effect of Deferoxamine on Trajectory of Recovery After Intracerebral Hemorrhage: A Post Hoc Analysis of the i-DEF Trial. Issue 7 (22nd March 2022) - Foster, Lydia; Robinson, Laura; Yeatts, Sharon D.; Conwit, Robin A.; Shehadah, Amjad; Lioutas, Vasileios; Selim, Magdy; ,
Abstract : Background: There are limited data on the trajectory of recovery and long-term functional outcomes after intracerebral hemorrhage (ICH). Most ICH trials have conventionally assessed outcomes at 3 months following the footsteps of ischemic stroke. The i-DEF trial (Intracerebral Hemorrhage Deferoxamine Trial) assessed modified Rankin Scale (mRS) longitudinally at prespecified time points from day 7 through the end of the 6-month follow-up period. We evaluated the trajectory of mRS among trial participants and examined the effect of deferoxamine on this trajectory. Methods: We performed a post hoc analysis of the i-DEF trial, a multicenter, randomized, placebo-controlled, double-blind, futility-design, phase 2 clinical trial, based on the actual treatment received. Favorable outcome was defined as mRS score of 0–2. A generalized linear mixed model was used to evaluate the outcome trajectory over time, as well as whether the trajectory was altered by deferoxamine, after adjustments for randomization variables, presence of intraventricular hemorrhage, and ICH location. Results: A total of 291 subjects were included in analysis (145 placebo and 146 deferoxamine). The proportion of patients with mRS score of 0–2 continually increased from day 7 to 180 in both groups (interaction P <0.0001 for time in main effects model), but treatment with deferoxamine favorably altered the trajectory (interaction P =0.0010). Between day 90 and 180, the deferoxamine group improved ( P =0.0001), whereas there was not significant improvement in the placebo arm ( P =0.3005). Conclusions: A large proportion of patients continue to improve up to 6 months after ICH. Future ICH trials should assess outcomes past 90 days for a minimum of 6 months. In i-DEF, treatment with deferoxamine seemed to accelerate and alter the trajectory of recovery as assessed by mRS. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02175225.